IMPACT OF THE AUDIT ON THE TRANSPARENCY AND DISCLOSURE OF FINANCIAL INFORMATION: AN ANALYSIS OF AN AUDITED COMPANY - Alejandro Ortiz Bordón, Iván; Darío Olivera Garay, Alexis; Ferreira Esquivel, Brigido; David Cano Gonzalez, Hernán; Godoy Páez, Eva (Revista Gênero e Interdisciplinaridade, 2023)
This research work focuses on auditing and its impact on companies. The general objective is to exhaustively analyze the “impact of auditing on the transparency and disclosure of financial information in companies” by conducting interviews with an auditor to know her opinion on the importance of the audit and the positive impact that companies have when applying it. To achieve this objective, a qualitative approach was used. The mandatory tax audit is a legal requirement and not an option, its value is established by the SET and must be requested. According to the suppliers, the accounting is rated with a “5”. The audited companies provide additional details, such as purchase forms by items or areas and by type of products, which increases the reliability of financial information.Auditors monitor the implementation of policies and procedures, identify errors and poor practices, and offer recommendations for improvements. Although auditing is not the only source for investment decisions, more than 85% of investors consider it. Interpersonal relationships improve significantly with the auditors’ opinion, increasing the transparency of the company. It is suggested that the audit should be carried out without being mandatory to have a greater impact. The audited companies must know the technical control standards to comply with them rigorously, and the results The final results of the audits must be objective, comply with the technical processes and the law. In conclusion, this research work provides valuable information on the implementation of the audit in companies.